2001
DOI: 10.1177/146135570100300403
|View full text |Cite
|
Sign up to set email alerts
|

Marksmanship Skills of Female Police Recruits: Impact of Basic Firearms Training

Abstract: Female police cifficers generally have a weaker grip strength and are lessfamiliar with firearms than their male counterparts when they enter the police academy. The study examined whether the basic law enforcementfirearms class adequately prepared female cifficers. Police recruits coming to the Police 'Training Institute (PTI) with no or little firearms training were selected. The grip strength and marksmanship scores of216 police recruits (185 men and 31 women) were measured. Both male and female recruits si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…Supporting the findings of our study, other studies [ 1 , 9 , 35 , 36 ] have likewise found that marksmanship scores on the qualifying firearms test were significantly correlated to maximal grip strength. These studies included marksmanship tasks with a Glock pistol [ 9 , 35 , 36 ], Beretta pistol [ 1 , 35 ], or Smith and Wesson revolver [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Supporting the findings of our study, other studies [ 1 , 9 , 35 , 36 ] have likewise found that marksmanship scores on the qualifying firearms test were significantly correlated to maximal grip strength. These studies included marksmanship tasks with a Glock pistol [ 9 , 35 , 36 ], Beretta pistol [ 1 , 35 ], or Smith and Wesson revolver [ 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…Supporting the findings of our study, other studies [ 1 , 9 , 35 , 36 ] have likewise found that marksmanship scores on the qualifying firearms test were significantly correlated to maximal grip strength. These studies included marksmanship tasks with a Glock pistol [ 9 , 35 , 36 ], Beretta pistol [ 1 , 35 ], or Smith and Wesson revolver [ 36 ]. Of particular note, the correlation between maximal grip strength and marksmanship scores in the study of Anderson and Plecas [ 1 ] was remarkably similar to the results of this study (Anderson, r = 0.38, p < 0.05; this study r = 0.398, p < 0.0001).…”
Section: Discussionsupporting
confidence: 92%
“…Correlational research has demonstrated that people perceive female officers differently than male officers along gender stereotypical lines. While attending a police academy, male (but not female) recruits perceived female recruits to be inferior despite relatively equal performance evaluations (Charles, 1981). A sample of prisoners perceived female correction officers to be more professional than male officers because they were able to keep calm in difficult situations (Boyd & Grant, 2005).…”
Section: Female Use-of-force: Violating Gender Stereotypesmentioning
confidence: 99%
“…As a result of the importance of fitness on these tasks, several studies have investigated the relationship between police officers' level of fitness and job performance (2,9,13,20,36,42,44). Some of the fitness tests commonly used in these studies to determine potential job performance included maximal and submaximal muscular strength measures using both machines (2) and dynamometers (9,13,26,42,44), aerobic capacity tests using V Ȯ2 max tests (42,44), 2.4-km timed runs (20,25), and shuttle run tests (13,28), muscular endurance assessments using push-ups (2,13,20,44), sit-ups (2,13,20,23), and pull-ups (13,20,25), power measures using a vertical jump (2,13,21), and agility tests (3,5,8,13,24). The general findings of these studies suggest a positive correlation between fitness tests results and police officer job performance (2,13,20,36,42).…”
Section: Introductionmentioning
confidence: 99%
“…Although various fitness tests are used to determine police officers' job performance in the literature (2,3,6,9,13,36,42), links between the PAT and PCT have yet to be investigated. Therefore, the aim of this research was to investigate the relationship between the PAT and the PCT to determine the usability of the PAT as a predictor of police academy trainees' performance on the PCT.…”
Section: Introductionmentioning
confidence: 99%